How triathletes hold-ride the bike through boxes during the first transition. A proposal of classification - Fernandez-Rodriguez, E.; Merino-Marban, R.; Romero Ramos, O.; Cullimore, J. A. (Journal of Physical Education and Sport, 2015)
A proposal is submit for the classification referring to the way in which triathletes carry their bicycles into the boxes during the first transition (T1). This area must be covered on foot carrying the bicycle next to you. The demonstration was made up by the participants of three Spanish Championships and age groups of different distances and types (407 triathletes). They were recorded on film from the time they took their bikes down and moved through the boxes. This study is only going to concentrate on what happens in the last part of T1. It`s the moment in which, having everything necessary to peddle, the triathlete picks up their bike, and travels through the transition area carrying the bike next to them as fast as possible. The purpose is to determinate how the binomial triathlete-bicycle was moved into the transition area, (hold-riding), in other words, in which part of the bike they put their hands. It was concluded that there were four habitual types of hold-riding bikes in the transition area.